Kinetika Enzim Nitrilase Dari Sel Utuh Rhodococcus spp Pada Biotransformasi Mandelonitril - R. Haryo Bimo Setiarto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Rhodococcus spp can be used as mandelonitrile substrate for carbon and nitrogen source in life cycle of metabolism. They have potential of activity biotransformation for produced (R/S)-mandelic acid from mandelonitrile. (R/S)-mandelic acid is an important biotransformation product for production of pharmaceuticals such as semisynthetic penicillins, cephalosporins, antitumor agents, antiobesity agents and antiinflamation agents. This research was conducted to determine the enzyme kinetics (Km and Vmax) of nitrilase from Rhodococcus TPIK, LP3, GLB5 (induction acetonitrile 1000 mM - mandelonitrile 100 mM) with florometric methods, spectrophotometer analysis (λ = 413 nm). This research was carried out by assaying nitrilase enzyme activities in various concentration of mandelonitrile subtrates which were between 10 mM – 100 mM with 10 mM interval. The result showed that the enzyme kinetics of nitrilase from Rhodococcus TPIK (Km was 72.303 mM and Vmax was 2.075 mM/ml cell/minute), Rhodococcus LP3 (Km was 47.048 mM and Vmax was 1.942 mM/ml cell/minute), Rhodococcus GLB5 (Km was 34.375 mM and Vmax was 2.083 mM/ml cell/minute). Nitrilase enzyme from Rhodococcus GLB5 have smallest Km value. So we can interpretationed, this enzyme have good complexity Enzyme-Substrate, high affinity with substrate, and high speed reaction for forms product mandelic acid.